Perspectives and Misconceptions about Frugal Engineering in Advanced Product Development: An Industry Insight - Timo Achtelik; Kanzy Abdalla; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2025)
Frugal innovation and frugal engineering are becoming increasingly important in both academic and practical discussions in the face of various economic, social and environmental pressures. Despite numerous positive associations and opportunities of frugality in the corporate environment, the discourse is still characterized by several barriers and enablers that impede a broad diffusion. In our paper, we contrast these barriers and enablers using a mix of industry evidence from action research and interview studies. In doing so, we highlight common misconceptions in the conceptual understanding of frugal engineering and create new perspectives on frugal product development specifically for practitioners in the field.
Keywords: 650; Frugal Engineering; Frugal Innovation